Religious Affiliation and Ethics: Patterns Regarding Beliefs for Workplace Behaviour - Fogel , Joshua; McSween , Nadine; Dutt , Osman (Journal of Law and Governance, 2010)
Ethical decisions are made regarding day-to-day workplace behaviours. We surveyed 315 college students from 9 different religious categories: Catholic, Christian, Jewish, Muslim, Hindu, Buddhist, Agnostic, Atheist, and Other. Individuals were asked whether “in the workplace, it is acceptable to do so” for 27 different behaviours. Those who were Hindu or Catholic consistently had scores indicating beliefs in performing more ethical behaviour. Those who were Buddhist or Atheist consistently had scores indicating beliefs in performing less ethical behaviour. In the analysis relating to 5 items regarding computer and Internet behaviours, those who were Jewish had scores indicating beliefs in performing less ethical behaviour. Managers who supervise young adults who recently graduated from college can be aware of possible ethical concerns facing those of different religions. They can mentor these individuals beginning their careers to adapt appropriate ethical behaviours for their job.